Posttransplant epithelioid inflammatory myofibroblastic sarcoma: A case report - Ritu Garg; Sumaid Kaul; Deepshikha Arora; Vikas Kashyap (Indian Journal of Pathology and Microbiology, 2019)
Epithelioid inflammatory myofibroblastic sarcoma (EIMS) is a rare entity and a novel variant of inflammatory myofibroblastic tumor (IMT), usually seen in children and nonsmoking young adults. Their occurrence in a posttransplant setting is still rare. These tumors are characterized by prominent epithelioid morphology, large histiocytoid “Reed Sternberg”-like cell, unique pattern of ALK immuno-reactivity, and aggressive clinical behavior. Their etiology and metastatic potential is controversial. In a post-transplant setting, many factors such as trauma, infections with EBV, HIV, Hepatitis C, mycobacteria, fungus, and chemotherapy-induced immunosuppression have been implicated in their etiology. We present the case of a 2-year-old female child who developed multiple omental and mesenteric tumor nodules, 8 months post liver transplant for progressive familial intrahepatic cholestasis (PFIC). Following a histopathological diagnosis of “mesenchymal neoplasm of possible malignant nature” on a trucut biopsy and frozen section, tumor debulking was performed. A final histological diagnosis of EMIS was made on the completely resected tumor. The patient remains in remission nearly 7 months after presentation, without any follow-up systemic chemotherapy. IMT after a solid organ transplant is rare, only 5 cases have been reported in the literature until now. Similar phenomenon has also been noted with hematopoietic stem cell transplant. However, to our knowledge, this case of EMIS in a post liver transplant patient is first of its kind.